Physical and psychological violence victimization scale in adolescents dating: Confirmatory factor analysis and Rasch model - Suci Musvita Ayu; Erni Gustina; Liena Sofiana; Yuniar Wardani; Moh Irma Sukarelawan (Institute of Advanced Engineering and Science, 2023)
This study aimed to assess the psychometric properties of physical and psychological violence victimization (PPVV) scales in adolescent dating. The PPVV scale consists of 37 items (17 items of physical violence and 20 items of psychological violence), with a 4-point Likert rating scale. A total of 682 students met the inclusion criteria as respondents (88.56% female, 11.44% male). Respondents are in the age range of 15-24 years and from the first year of college to the fourth year. The results showed that two items did not fit statistically, and six were biased toward the respondent’s attributes. The average difficulty level of the item is higher than the respondent’s ability level. The PPVV instrument developed shows unidimensionality. Meanwhile, the four rating scales used have not shown satisfactory performance. They need to be simplified into three scales. However, analysis of the confirmatory factor analysis (CFA) and Rasch model shows that the PPVV scale has a good factor structure and psychometric properties as a measuring tool. So, the PPVV instrument can be used by future researchers by eliminating PhyV11 and PhyV16 and using a three-level rating scale.